Genetic Variation of Groundnut (Arachis hypogaea L.) Genotypes in Semi-Arid Zone Sudan - Sabiel, Salih AI; Ismail, Mohamed I; Abdalla, Elgailani; Osman, Khalid A (International Journal of Environment, 2014)
Twelve genotypes of groundnut (Arachis hypogaea L.) were executed under rain-fed conditions in a semi-arid zone at the Research farm of El Fasher Research Station, Sudan for two consecutive seasons 2006 and 2007. Genotypic and phenotypic variability, heritability in a broad sense and genetic advance were estimated in a randomized complete block design with four replications. High heritability estimate (above 95 %) was recorded by hay yield (kg/ha) in both seasons and 100- seed weight in season 2006. Moreover, the high genetic advance was recorded for hay yield (kg/ha) and pod yield (kg/ha) in both seasons. However, a day to 50% flowering was expressed low genotypic coefficient of variation with low genetic advances in both seasons. Highly significant different among genotypes were found for days to 50% flowering, hay yield (kg/ha), shelling (%), while pod yield (kg/ha) and 100- seed weight were observed non-significant. The high yielding genotype was ICGV93260 with a pod yield of 1389.1 kg/ha. Pod yield (kg/ha) was highly significantly and positively correlated with hay yield (kg/ha), shelling (%) and 100- seed weight, while non-significant and negative correlated with days to 50% flowering. Based on the results the characters hay yield (kg/ha), shelling (%), 100- seed weight and days to 50% flowering to be the important characters which would be used in selection for groundnut improvement. The promising genotype identified in this study could provide valuable sources of resistance to climate-change-related stresses and for other consequent breeding activities in groundnut improvement. DOI: http://dx.doi.org/10.3126/ije.v3i3.11060 International Journal of Environment Vol.3(3) 2014: 16-23